Learn to code by solving problems : a Python programming primer - Zingaro, Daniel (San Francisco, CA : No Starch Press, 2021)
"Teaches readers how to use Python to solve short, situational competitive programming problems. Each chapter requires the reader to learn a new feature or function of Python in order to solve a problem, while emphasizing basic programming concepts, problem-solving strategies, and critical thinking skills"--
Includes index.
CSE
Book Finder International
Keywords: Python (Computer program language).; Computer programming; Computer science